Introducing Types of Scientific Publications to the Elementary School Teachers in Pontianak Municipality - Citra Suryanovika; Mita Nur Aflah (International Journal of Public Devotion, 2022)
Publication of scientific paper becomes a common issue of Elementary School teachers because they should understand journal templates and ojs based journal system to submit an article. Team of STBA Pontianak held a community outreach to introduce kinds of scientific paper publication to all teachers in Pontianak City in the form of Seminar. This activity invited a certified teacher who have published many books and article journals. She motivated teachers to publish books. There was also a direct practice of identify OJS based journals. According to the evaluation, two materials of the activity were a new knowledge for almost all participants. In other words, they have not learned about the materials elsewhere before. It can be concluded that all participants need further practice in preparing their research paper, and in submitting it to the journal